TEACHER PERCEPTION TOWARDS THE USE OF CODE SWITCHING IN EFL CLASSROOM: A CASE STUDY IN ENGLISH INTENSIVE PROGRAM AT STATE ISLAMIC INSTITUTE IN CIREBON - Royani Afriani (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
The present study is descriptive qualitative research. The study aims to investigate and show the teachers perceptions toward the use of code-switching (CS) used by teachers in EFL classroom, especially in English intensive program at a State Islamic Institute. A four-section 20-item questionnaire was developed and distributed to the teachers. The data from the questionnaire were analyzed. The results display that teachers' perceptions are positive towards the use of code-switching in the EFL classroom. Teachers believe that the use of code-switching could help them in eliciting content, manage the classroom, and show interpersonal relations in the classroom. However, the use of code-switching is beneficial for learners but it also needs limitation because it could damage the process of language acquisition as learners don't get comprehensive input.